Characterization and genetic analysis of extensively drug-resistant hospital acquired Pseudomonas aeruginosa isolates - Abdelaziz, Mai A.; El-Aziz, Abeer M. Abd; El-Sokkary, Mohamed M. A.; Barwa, Rasha (BMC microbiology, 2024)
The incidence of hospital-acquired infections in extensively drug-resistant Pseudomonas aeruginosa (XDR-PA) has been increasing worldwide and is frequently associated with an increase in mortality and morbidity rates. The aim of this study was to characterize clinical XDR-PA isolates recovered during six months at three different hospitals in Egypt. Seventy hospital-acquired clinical isolates of P. aeruginosa were classified into multidrug-resistant (MDR), extensively drug-resistant (XDR) and pandrug-resistant (PDR), according to their antimicrobial resistance profile. In addition, the possession of genes associated with mobile genetic elements and genes encoding antimicrobial resistance determinants among isolates were detected using polymerase chain reaction. As a result, a significant percentage of the isolates (75.7%) were XDR, while 18.5% were MDR, however only 5.7% of the isolates were non-MDR. The phenotypic detection of carbapenemases, extended-spectrum β-lactamases (ESBLs) and metallo β-lactamase (MBL) enzymes showed that 73.6% of XDR-PA isolates were carbapenemases producers, whereas 75.5% and 88.7% of XDR-PA isolates produced ESBLs and MBL respectively. In addition, PCR screening showed that oxa gene was the most frequently detected gene of carbapenemases (91.4%), while aac(6')-lb gene was mostly detected (84.3%) among the screened aminoglycosides-resistance genes. Furthermore, the molecular detection of the colistin resistance gene showed that 12.9% of isolates harbored mcr-1 gene. Concerning mobile genetic element markers (intI, traA, tnp513, and merA), intI was the highest detected gene as it was amplified in 67 isolates (95.7%). Finally, phylogenetic and molecular typing of the isolates via ERIC-PCR analysis revealed 10 different ERIC fingerprints. The present study revealed a high prevalence of XDR-PA in hospital settings which were resistant to a variety of antibiotics due to several mechanisms. In addition, 98% of the XDR-PA clinical isolates contained at least one gene associated with movable genetic elements, which could have aided the evolution of these XDR-PA strains. To reduce spread of drug resistance, judicious use of antimicrobial agents and strict infection control measures are therefore essential.